Elite female football players` perception of the impact of their menstrual cycle stages on their football performance. A semi-structured interview-based study - Read, P.; Mehta, R.; Rosenbloom, C.; Jobson, E.; Kryger, K. O. (Science and Medicine in Football, 2022)
Objectives: This study assesses how female footballers perceive how their menstrual cycle impacts their physical and psychological performance, informing future research and intervention. Methods: Semi-structured interviews, developed using piloting and peer review took place with fifteen elite female footballers from two English WSL clubs (age: 25.2 [18-33]). Data was audio recorded, transcribed verbatim, and analysed thematically using NVivo. Results: All players (100%) perceive their menstrual cycle to negatively impact performance. Analysing 27,438 words of data revealed five themes: A) symptoms, B) preparation, C) performance, D) recovery, and E) management. Over half (53%) of players experienced decreased appetite and sleep quality prior to performance during menstruation. Competitive performance was perceived to be most negatively impacted during menses (54 references) following by the pre-menstrual stage (23 references). During menstruation, the most impacted physical performance indicators were power (93%) and fatigue (87%). Psychologically, confidence, focus, and reaction to criticism were commonly affected (66.7%). Players reported missing training (13.3%) and matches (13.3%) due to severity of impact. Recovery was affected during the pre-menstrual (26.7%) and menstrual (66.7) stages. Players self-manage symptoms using over the counter (66.7%) and prescription (26.7%) medication, some prophylactically prior to competition (46.7%). Conclusions: This first attempt to ascertain player perception in football exposes a clear negative impact on performance. The complex interplay of biopsychosocial and logistical factors, lack of awareness and education highlight the need for further research. Intervention is necessary and immediate initiation would be prudent, starting with simple measures such as basic self-management advice, education, and provision of sanitary products.